IoT-Based System for Real-Time Swimming Pool Water Quality Monitoring - Jemat A.; Yussof S.; Sameon S.S.; Alya Rosnizam N.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Flow of water; Lakes; Maintenance; Monitoring; Portals; Water quality; Maintenance tasks; Maintenance work; Pool water; Pool water qualities; Real- time; Sensor; Swimming pool water; Water monitoring systems; Water quality monitoring systems; Water quality parameters; Internet of things